Demographic trends in the incidence of malignant appendiceal tumours in England between 1995 and 2016: Population-based analysis. Issue 4 (27th August 2022) - Orchard, Philippa; Preece, Ryan; Thomas, Michael G; Dixon, Steven W; Wong, Newton A C S; Chambers, Adam C; Messenger, David E
Abstract: Aims: Recent data suggest that the incidence of malignant appendiceal tumours is increasing. This study aimed to determine temporal trends in the incidence of malignant appendiceal tumours within England and a possible influence by demographic factors. Methods: All incident cases of appendiceal tumours in patients aged 20 years and above were identified from the National Cancer Registration and Analysis Service database between 1995 and 2016 using ICD-9/10 codes. Cancers were categorized according to histology. Joinpoint regression analysis was used to investigate changes in age-standardized incidence rates by age, sex, histological subtype and index of multiple deprivation quintiles, based on socioeconomic domains (income, employment, education, health, crime, barriers to housing and services and living environment). Average annual per cent changes (AAPCs) were estimated by performing Monte-Carlo permutation analysis. Results: A total of 7333 tumours were diagnosed and 7056 patients were analysed, comprising 3850 (54.6 per cent) neuroendocrine tumours (NETs), 1892 (26.8 per cent) mucinous adenocarcinomas and 1314 (18.6 per cent) adenocarcinoma (not otherwise specified). The overall incidence of appendiceal tumours increased from 0.3 per 100 000 to 1.6 per 100 000 over the study interval. Incidence rate increases of comparable magnitude were observed across all age groups, but the AAPC was highest among patients aged 20–29 years (15.6 per cent, 95 per cent c.i 12.7–18.6 per cent) and 30–39 years (14.2 per cent, 12.2–16.2 per cent) and lowest among those aged 70–79 years (6.8 per cent, 5.7–8.0 per cent). Similar incidence rate increases were reported across all socioeconomic deprivation quintiles and in both sexes. Analysis by grade of NET showed that grade 1 tumours accounted for 63 per cent between 2010 and 2013, compared with 2 per cent between 2000 and 2003. Conclusions: The incidence rate of malignant appendiceal tumours has increased significantly since 1995 and is mainly attributed to an increase in NETs. The increased diagnosis of low-grade NETs may in part be due to changes in pathological classification systems. Abstract : North American studies have shown that appendiceal tumours are increasing in all histological subtypes and ages groups. This paper is the first to show this in a European population and is important given the current debate regarding conservative management of appendicitis.